Relation entre le corps vécu et le corps vivant après un effort et une procédure de récupération par immersion en eau froide ou passive chez des joueuses de handball - Tourny, C.; Castres, I.; Tabben, M.; L`Hermette, M.; Ghoul, N.; Andrieu, B.; Coquart, J. (Movement & Sport Sciences - Science & Motricité, 2018)
The objective of this study was to highlight the afferent inputs between the living body and body experienced from two types of recovery method after a handball training session. The eight female handball players included in the study were playing in the national division of the French championship. They randomly realized a passive recovery and a cold immersion one after the training session. During the recovery time, the body sensations and the physiological data were collected. Moreover, verbatim reports were set up one day after. The results demonstrated a powerful tie between living and lived bodies. Furthermore, it should be interesting to identify the respondent members by considering the lived body.